Limnology and Aquatic Birds Proceedings of the Fourth Conference Working Group on Aquatic Birds of Societas Internationalis Limnologiae (SIL), Sackville, New Brunswick, Canada, August 3-7, 2003 - Hanson, Alan R.; Kerekes, Joseph J. (Developments in Hydrobiology, 2006)
The importance of habitat conservation for the protection of birds has become widely acknowledged and accepted by natural resource managers and the general public. Papers presented in this volume further our understanding of the important role that limnology has in determining habitat suitability for waterbirds. Long-term population monitoring of waterbirds is an important tool in our quest to understand the role waterbirds play in their environment. Continued population declines of many species of aquatic birds indicate the need for additional understanding of how human activities negatively impact water quality and bird populations and what mitigative actions can be taken. The main objective of the Working Group on Aquatic Birds of the International Limnological Society (SIL) is to integrate waterbirds into hydrobiology and treat waterbird studies in a limnological context. To achieve this goal, the Working Group organizes conferences to facilitate communications among limnologists interested in aquatic birds and ornithologists interested in the aquatic habitat. The efforts of the SIL Working Group on aquatic birds has resulted in a new emphasis on the links between aquatic birds and their environment. This book is international in scope and presents information on species as diverse as common loon, harlequin duck, and semi-palmated sandpiper, and locations ranging from Iceland to Japan.